Vitamin K and vascular calcification in chronic kidney disease: An update of current evidence - Yu-Li Lin; Bang-Gee Hsu (Tzu Chi Medical Journal)
Vascular calcification, characterized by calcium deposition in the intimal and medial layers of the arterial wall, is frequently encountered in patients with chronic kidney disease (CKD) and leads to an enhanced risk of adverse cardiovascular (CV) outcomes. However, the underlying complex pathophysiology remains incompletely understood. Recently, Vitamin K supplementation aimed at correcting Vitamin K deficiency highly prevalent in CKD holds great promise to mitigate the progression of vascular calcification. This article discusses the functional Vitamin K status in CKD, the pathophysiology linking Vitamin K deficiency and vascular calcification, and reviews current literature from animal models, observational studies, and clinical trials across the different spectrum of CKD. While favorable effects of Vitamin K on vascular calcification and CV outcomes are suggested in animal and observational studies, most recently published clinical trials investigating the effects of Vitamin K on vascular health failed to support the beneficial role of Vitamin K supplementation, despite improving the functional status of Vitamin K. We address the potential reasons for these discrepancies and provide further perspective on Vitamin K research in CKD.